PARTISIPASI ISTRI NELAYAN DALAM MENINGKATKAN PENDAPATAN RUMAH TANGGA DI KORONG SUNGAI LIMAU KABUPATEN PADANG PARIAMAN PROVINSI SUMATERA BARAT - Heri Oktofriyadi; Firman Nugroho; Kusai ' (Berkala Perikanan Terubuk, 2014)
ABSTRACTThis study was conducted on December 2013. It was aimed at finding out of the involvement of fisherman wives in terms of time allocated to increase the domestic incomes and the their participation in terms of domestic incomes. The method used in this study was census method with 22 respondents. The fisherman wives involvement observed from the number of working hours devoted to increase the domestic incomes shows that the fishermen’s working hours is higher than their wives. The wives contribution to the domestic income by average contribution on the level of 26-50 %.Keywords: Fisherman’s wives participation, income participation of fisherman’s wives, Desa Korong Sungai Limau.